Factors Associated With Pain Experience Outcome in Knee Osteoarthritis. Issue 12 (December 2014) - Rayahin, Jamie E.; Chmiel, Joan S.; Hayes, Karen W.; Almagor, Orit; Belisle, Laura; Chang, Alison H.; Moisio, Kirsten; Zhang, Yunhui; Sharma, Leena
<x xml:space="preserve">Abstract</x> Objective Few strategies to improve pain outcome in knee osteoarthritis (OA) exist in part because how best to evaluate pain over the long term is unclear. Our objectives were to determine the frequency of a good pain experience outcome based on previously formulated OA pain stages and test the hypothesis that less depression and pain catastrophizing and greater self‐efficacy and social support are each associated with greater likelihood of a good outcome. Methods Study participants, all with knee OA, reported pain stage at baseline and 2 years. Baseline assessments utilized the Geriatric Depression Scale, Pain Catastrophizing Scale, Arthritis Self‐Efficacy Scale, and Medical Outcomes Study social support survey. Using pain experience stages, good outcome was defined as persistence in or movement to no pain or stage 1 (predictable pain, known trigger) at 2 years. A multivariable logistic regression model was developed to identify independent predictors of a good outcome. Results Of 212 participants, 136 (64%) had a good pain outcome and 76 (36%) a poor pain outcome. In multivariable analysis, higher self‐efficacy was associated with a significantly higher likelihood of good outcome (adjusted odds ratio [OR] 1.14 [95% confidence interval (95% CI) 1.04–1.24]); higher pain catastrophizing was associated with a significantly lower likelihood of good outcome (adjusted OR 0.88 [95% CI 0.83–0.94]). Conclusion This stage‐based measure provides a meaningful and interpretable means to assess pain outcome in knee OA. The odds of a good 2‐year outcome in knee OA were lower in persons with greater pain catastrophizing and higher in persons with greater self‐efficacy. Targeting these factors may help to improve pain outcome in knee OA.